Doping GeSb2Te4 with Cr3+: Structure and Temperature‐Dependent Physical Properties1. Issue 12 (18th August 2015) - Welzmiller, Simon; Schlegel, Robert; Pöppl, Andreas; Bothmann, Georg; Scheidt, Ernst‐Wilhelm; Scherer, Wolfgang; Oeckler, Oliver
Abstract: The tellurides Ge0.94 Cr0.04 Sb2 Te4 and Ge0.88 Cr0.08 Sb2 Te4 were synthesized in sealed silica glass ampoules. Rietveld refinements show that they crystallize in the 21 R ‐In3 Te4 structure type ( R 3 m ), similar to undoped GeSb2 Te4 . The composition and phase purity were confirmed by ICP‐AES as well as by SEM and TEM, including EDX measurements. EPR spectroscopy reveals the valence state +III for the Cr atoms ( g = 1.990) in Ge0.88 Cr0.08 Sb2 Te4, which agrees well with the Cr 3+ content calculated from the inverse magnetic susceptibility. The material exhibits a ferromagnetic fluctuations with a paramagnetic Curie temperature of 70 K ± 20 K and is a metallic conductor. Compared to GeSb2 Te4, the electrical conductivity is increased by a factor of 2.5. As Cr doping further leads to a higher Seebeck coefficient, the thermoelectric figure of merit ZT reaches values of up to 0.3 at 500 °C, i.e. three times the value of undoped material. Abstract :